Patterns Of Educative Interaction In The Quran And Its Contribution To Islamic Education (Study Of Stories In The Quran) - Saputra, Imron Bima; Nahar, Syamsu; Zein, Achyar (Sekolah Tinggi Agama Islam Al Hidayah, 2023)
This research aims to analyze: 1) the interaction patterns of story verses in the Alquran, 2) the relevance of the interaction of story verses in the Alquran to Islamic education, and 3) the contribution of the interaction patterns of story verses in the Alquran to Islamic education. This type of research is qualitative, and the approach used in this research is the Mauḍū'i interpretation method. The data sources in this research consist of two data sources, namely primary and secondary. The research results show that: 1) The interaction patterns of story verses in the Alquran have three patterns, namely one-way, two-way and three (multi) direction interaction patterns. 2) The educational interaction on the stories in the Alquran is very complete and comprehensive, in general the theory it conveys has relevance, especially to Islamic education and family education, so it is still very relevant to be used as a guide for teachers and parents today in order to realize education with character. 3) Contribution of educational interactions towards providing contributions in terms of science, knowledge and insight to families and schools through the nature and meaning of educational interaction patterns in verses of the Alquran, including: a) Making parents good communicators, b) The importance of understanding the urgency of language choice and appropriate communication techniques, c) Providing enlightenment through educational interactions between teachers and students by developing students' spiritual empowerment and also their morality, both personal and group, d) Educational interactions can build character between communicators and communicants, e) Educative interactions as competency development teacher learning methods, f) As a teacher evaluation in determining the interaction patterns that will be used according the type of lesson material.